Turbulence : A Corporate Perspective on Collaborating for Resilience - Kupers, Roland, 1959-; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2019)
The ever tighter coupling of our food, water and energy systems, in the context of a changing climate is leading to increasing turbulence in the world. As a consequence, it becomes ever more crucial to develop cities, regions, and economies with resilience in mind. Because of their global reach, substantial resources, and information-driven leadership structures, multinational corporations can play a major, constructive role in improving our understanding and design of resilient systems. This volume is the product of the Resilience Action Initiative, a collaboration among Dow, DuPont, IBM, McKinsey & Co., Shell, Siemens, Swiss Re, Unilever, and Yara designed to explore possible corporate contributions to global resilience, especially at the nexus of water, food and energy. Aggressively forward-thinking, and consistent with an enlightened self-interest, the ideas considered here represent a corporate perspective on the broad collaborations required for a more resilient world.
The resilience action initiative: an introduction / Maike Böggemann and Norbert Both -- A pragmatic frame to explore resilience / Marco Albani and Roland Kupers -- A resilience lens for enterprise risk management / David N. Bresch, Jaap Berghuijs, Rainer Egloff and Roland Kupers -- Multi-sector collaboration for resilience / Mark Smith -- Building resilience through teamwork Seven tips to make it work / Marco Albani and Kimberly Henderson -- The case for green infrastructure / Neil C. Hawkins and Glenn Prickett -- Nexus! Resilience in a pressure cooker / Herman van der Meyden -- Getting to resilience from the bottom-up / Thekla Teunis -- Corporations and Resilience / Simone Arizzi, Maximilian Egger, Dawn Rittenhouse and Peter Williams.
Issued as part of book collections on Project MUSE.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Corporations; Sustainable development; Electronic books